Improving Medical Wellness with Halal and Thayyib Certification in Traditional Health Services: A Literature Review - Riskha Dora Candra Dewi; Suryono (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Halal and thayyib certifications are generally used to certify that food products adhere to Islamic rules. "Halal" refers to what is permitted or halal in Islam, whereas "Thayyib" emphasizes goodness, safety, and responsible sourcing. However, certification can be applied to a variety of commodities and services, including traditional health services. Traditional healing services must be developed in a complete manner that respects cultural variety, stimulates collaboration among many healing traditions, assures quality and safety standards, and prioritizes community involvement and empowerment. Aims: This study examines thayyib and halal certification as a means of improving traditional health service promises and achieving medical wellness. Method: The present study employs a literature review methodology, drawing on national and international journals published between 2019 and 2023. The journal sources consulted for this research encompass PubMed, Google Scholar, Elsevier, and Research Gate. Result: The findings indicate that common beliefs about moral sourcing, religious compliance, and holistic health promotion underpin the association between halal and thayyib certification and medical health. Providers can deliver services that prioritize the safety, quality, and well-being of people as well as the community as a whole while still adhering to religious restrictions by incorporating this accreditation into their medical operations. Conclusion:  In summary, the relationship between medical wellness and certifications for halal and thayyib highlights the value of cultural sensitivity, quality control, and comprehensive health promotion in healthcare services. Integrating this credential into medical practice allows healthcare professionals to serve a variety of patient populations better and advance inclusive, moral, and sustainable healthcare.